The Importance of the Active Role of the Congregation Pastor in Involving God's People in Serving God's Work - Sinlae, Demsi Yanto; Bulu, Dominggus Rina; Putralin, Eliantri; Manggoa, Ridolfroa S.Th; Mau, Marthen (Indonesian Journal of Advanced Research, 2024)
In general, some of God's people do not want to be involved in serving God's work. Therefore, congregational pastors need to educate, teach, develop and guide God's people so that they are involved in serving His work. The purpose of this research is to explain the importance of the active role of congregational pastors in involving God's people to serve God's work with full loyalty and responsibility so that the service of God's work can progress. The research methodology used is descriptive qualitative research methodology with a library research approach. The results of the research are that in essence God's work in the church has been going well, but congregational pastors continue to be required to involve God's people so that God's work continues to progress towards significant progress. The implication: congregational pastors must involve God's people in serving God's work in all church organizations.